Creating effective groups the art of small group communication - Fujishin, Randy (Rowman & Littlefield Publishing Group, Inc., 2023)
This practical book gives students the fundamental knowledge and skills necessary to communicate more effectively and interact more productively in the small group setting. With the help of this book, any group member can learn the skills necessary to participate in and lead a task group in an effective, productive, and healthy manner. The fourth edition features new content on communicating within virtual groups and conducting online meetings. -- Provided by publisher.